Nonlinear Dynamics : Mathematical Models for Rigid Bodies with a Liquid. - Lukovsky, Ivan A. (De Gruyter studies in mathematical physics., 2015)
This book is devoted to analytically approximate methods in the nonlinear dynamics of a rigid body with cavities partly filled by liquid. It combines several methods and compares the results with experimental data. It is useful for experienced and early-stage readers interested in analytical approaches to fluid-structure interaction problems, the fundamental mathematical background and modeling the dynamics of such complex mechanical systems.